Self-Emulsifying Drug Delivery System: Formulation And Evaluation - KAVITA MEHTA,; GANESH BORADE,; GANESH RASVE,; ARVIND BENDRE, (International Journal of Pharma and Bio Sciences, 2011)
The major problem in oral drug formulations is low and erratic bioavailability, which mainly results from poor aqueous solubility. This may lead to high inter- and intra subject variability, lack of dose proportionality and therapeutic failure. Due to this fact, many drug candidates fail to reach the market, although they exhibit potential pharmacodynamic activity or otherwise administered in higher doses, leading to the rise of toxicity problems. Self-emulsifying drug delivery systems (SEDDS) are usually used to improve the bioavailability of hydrophobic drugs. These are defined as isotropic mixtures of natural or synthetic oils, solid or liquid surfactants or, alternatively, one or more hydrophilic solvents and co-solvents/ surfactants. The system being thermodynamically stable requires low energy emulsification which will be provided by GI fluid agitation. The basic evaluation parameters studied for these systems are droplet size & morphology determination, emulsification time, zeta potential measurement, stability studies, in vivo and in vitro absorption studies.